Pengembangan Modul Laju Reaksi Berbasis Guided Discovery Learning untuk Kelas XI SMA atau MA - Abdul Rohim Harahap; Bayharti Bayharti (Universitas Negeri Padang, 2021)
The development and determination of module validity aims to examine the application of guided discovery learning model to the material reaction rate. The development was carried out using the plomp model with 3 stages, namely preliminary research, prototyping stage and assessment. The stages carried out are only up to the prototyping stage and formative evaluation until the expert review stage. Expert review is carried out through an assessment of 5 validators, namely 3 chemistry lectures and 2 chemistry teachers. Data were collected using a validity questionnaire which was then analysed the Aiken V formula. Based on the results, the resulting module has a valid category with a V value of 0,83 but its practicality has not been tested.